Menafsir Ulang Independensi Pers Dalam Perspektif Etika Media: Studi Literatur Atas Pemberitaan Politik Tempo - Lapina, Lena; Priatna, Achmad Nashrudin; Meira, Della; Puteri, Siti Abelia (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
Press independence is a fundamental principle in the practice of democratic journalism, particularly in political reporting, which is full of interests and power relations. However, in practice, press independence not only faces political pressure but is also influenced by the economic structure of the media and the dynamics of journalistic ethics. This article aims to reinterpret the concept of press independence within the framework of media ethics through a literature review of political reporting practices, focusing on Tempo as a representation of critical journalism in Indonesia. This study uses a qualitative approach with a literature study method, analyzing various academic sources, press regulations, and previous studies relevant to press independence, media ethics, and political reporting. The study results show that press independence cannot be understood as an absolute condition free from influence, but rather as an ethical practice that is dynamic and contextual. Tempo showing a form of ethical independence through the courage to take a critical stance based on facts and public interest, even under the pressure of economic and political media structures. Thus, press independence in political reporting is more accurately understood as the result of ongoing negotiation between the normative principles of journalism, media ethics, and the structural realities of the press industry. This study is expected to enrich academic discourse on media ethics and press independence in Indonesia.